Development of Urea Sensor Based on colorimetric method and Digital RGB Analysis - Fauziyah, Begum; Khoiriyah, Muslimatul; Hakim, Abdul; Wafi, Abdul (International Journal of Engineering and Technology, 2019)
A simple and low cost of urea sensor has been developed using diacetyl monoxime (DAM), Thiosemicarbazide (TSC), Sulfuric Acid and Phosphoric Acid to form pink-azo dye compoud. A urea sensor was manufactured by immobilizing reagents to the silica gel plate. The sensor was tested to determine urea in various concentrations including 0; 5; 6; 25; 26 and 80 mg/dL.Â  The color formed on the sensor was captured by Samsung camera 12 megapixel in the black box to obtain color digital data such as red, green, blue (RGB). The Î” Mean RGB valuess were 0.0; 51.6; 51.9; 58.5; 61.4 and 75.3 respectively.Â Â